Effects of augmented reality on perceived motivation for struggling readers: Mix-method analysis - Rengganis Siwi Amumpuni; Mustakim Sagita; Zaiturrahmi Zaiturrahmi (Journal of English Language Teaching Innovations and Materials (Jeltim), 2023)
Higher education students who struggle with reading may find some relief via the use of technology, especially new and developing forms of technology. Even though augmented reality (AR) has been used in the classroom with great success to motivate and engage children who are difficult to teach, there hasn't been a lot of research done on how augmented print may help those who have trouble reading. The purpose of this study is to investigate the effect of augmented reality on perceived motivation for students currently enrolled in higher education, namely their engagement with and understanding of an upgraded design theory book, as well as their perceived motivation to read. This research was conducted using the mix method approach, supported with some different methodologies. The findings reveal that increased support for academic literature enhances motivation, engagement, and confidence in understanding, impacting both struggling and proficient readers. We concluded that students, regardless of their reading level, expressed a willingness to use AR reading assistance for future books. Further research is crucial given the heightened levels of motivation and confidence. This research aligns with technological advancements, and educators can influence the development of augmented reality apps for classroom use. Future studies should focus on students with reading difficulties, exploring the optimal design of AR experiences and learning games to enhance understanding and retention of art history lectures in higher education